Penatalaksanaan Kasus Low Back Pain Melalui Terapi Akupunktur Pada Lansia Di Kelurahan Mangliawan Kabupaten Malang - Leny Candra Kurniawan; Ikhwan Abdullah; Chantika Mahadini (CV. Multi Kreasi Media, 2026)
Low Back Pain is one of the common musculoskeletal complaints frequently experienced by the elderly, and it can reduce their mobility as well as their overall quality of life. The problem identified in Mangliawan Village is that 70% of older adults experience joint pain that has not been optimally managed, along with a low level of public knowledge regarding non-pharmacological management. This community service activity aims to improve the management of Low Back Pain in the elderly by providing health education and acupuncture therapy. The methods used include a participatory approach, health education sessions, and the provision of acupuncture therapy in several sessions. The results of the activity show an increase in the elderly’s understanding of the causes, prevention, and management of Low Back Pain, as well as a reduction in pain intensity in 80% of participants and an improvement in their ability to perform daily activities. In addition, the level of participation and participant satisfaction was relatively high. This community service initiative is expected to improve the quality of life of the elderly through promotive and curative community-based approaches.